Evaluation of the Stratospheric and Tropospheric Bromine Burden Over Fairbanks, Alaska Based on Column Retrievals of Bromine Monoxide. Issue 2 (15th January 2021) - Wales, Pamela A.; Salawitch, Ross J.; Lind, Elena S.; Mount, George H.; Canty, Timothy P.; Chance, Kelly; Choi, Sungyeon; Donohoue, Deanna; Kurosu, Thomas P.; Simpson, William R.; Suleiman, Raid M.
Abstract: In spring 2011, columns of bromine monoxide (BrO) were retrieved over Fairbanks, Alaska using a ground‐based multifunction differential optical absorption spectroscopy (MFDOAS) instrument. MFDOAS vertical column BrO is consistently lower than retrievals from the satellite‐based Ozone Monitoring Instrument (OMI), with a relative bias of 20 ± 14%. Numerous tropical‐based studies suggest that 5 ± 2 parts per trillion (ppt) of bromine from very short‐lived substances (VSLS) reaches the stratosphere. We evaluate upper limits on the contribution of VSLS to stratospheric bromine by treating the column retrievals of BrO as purely stratospheric and modeling the ratio of BrO to total inorganic bromine. The OMI and MFDOAS retrievals respectively present 8 and 5 ppt upper limits on the stratospheric injection of VSLS, and kinetic uncertainties in the daytime partitioning of bromine species decrease both values by ∼1.7 ppt. The OMI‐based estimate is in agreement with the 5 ppt tropical‐based value for stratospheric injection of VSLS if the tropospheric column of BrO is 1.5 × 10 13 molecules cm −2 over Fairbanks, which is within the range of uncertainty of a second ground‐based instrument that monitored tropospheric BrO during the campaign. Because our ground‐based instruments detected no BrO near the surface, this value for tropospheric BrO would originate from higher altitudes in the troposphere and is in agreement with previous retrievals of background tropospheric BrO. Our calculations of tropospheric BrO over Fairbanks are most sensitive to uncertainties in the stratospheric loading of VSLS, followed by the difference between the OMI and MFDOAS retrievals of BrO. Key Points: Retrievals of column bromine monoxide (BrO) suggest upper limits for stratospheric injection of bromine from very short‐lived species are 4–8 ppt Satellite retrievals are consistent with injection of 5 ppt if tropospheric BrO is 1.5 × 10 13  cm −2 over Fairbanks, Alaska in spring 2011 Ground‐based vertical column BrO is 20% lower than satellite data and suggests tropospheric BrO is less than 1 × 10 13  cm −2 over Fairbanks